Kinetic Parameters of Platelet Aggregation as an Expression of Platelet Responsiveness - Rossi, Ennio C; Louis, Gerlinde (Thrombosis and Haemostasis, 1977)
The kinetics of platelet aggregation induced by collagen and by ADP were studied. The maximum aggregation (ΔLTmax) and the ADP and collagen concentrations required to produce half-maximum aggregation (Kd) were determined using platelets obtained from normal individuals, individuals who ingested aspirin and individuals whose platelet-rich plasma (PRP) demonstrated spontaneous aggregation. The Kd and ΔLTmaxfor ADP-induced platelet aggregation were variable and markedly affected by the citrate concentration. Conversely, kinetic parameters of collagen-induced aggregation were more reproducible and less affected by citrate. The Kd for collagen in platelet aggregation was increased following aspirin ingestion and decreased in samples of PRP that demonstrated spontaneous aggregation. These results suggest that kinetic parameters of platelet aggregation may be useful to express the responsiveness of platelets.